2013
DOI: 10.1016/j.pmrj.2013.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Patients With Low Back Pain Demonstrate Increased Activity of the Posterior Oblique Sling Muscle During Prone Hip Extension

Abstract: Women with CLBP had greater activity in the posterior oblique sling muscles than did women without CLBP during PHE. These findings suggest that an alteration can be made in posterior oblique sling muscle activities during PHE in women with CLBP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
33
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 31 publications
1
33
1
Order By: Relevance
“…2 Myofascial slings are interconnected muscle chains that lead to trunk stability during movement and force transmission from the lower to upper limbs. 3 Most muscle injuries occur in the same sling that leads to pain and imbalances and can provoke trigger points. A myofascial sling that plays a critical role in trunk extension is the posterior oblique sling, which is composed of erector spina, hamstring, gluteal maximus (GM), and latissimus dorsi muscles.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…2 Myofascial slings are interconnected muscle chains that lead to trunk stability during movement and force transmission from the lower to upper limbs. 3 Most muscle injuries occur in the same sling that leads to pain and imbalances and can provoke trigger points. A myofascial sling that plays a critical role in trunk extension is the posterior oblique sling, which is composed of erector spina, hamstring, gluteal maximus (GM), and latissimus dorsi muscles.…”
Section: Introductionmentioning
confidence: 99%
“…A myofascial sling that plays a critical role in trunk extension is the posterior oblique sling, which is composed of erector spina, hamstring, gluteal maximus (GM), and latissimus dorsi muscles. [3][4][5] The latissimus dorsi has a synergetic role with gluteus maximus through the thoracolumbar fascia in trunk extension. 6 Kim et al 3 reported a greater muscular activation pattern of latissimus dorsi in CLBP patients during prone hip extension test.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations